Sistem Pemasaran Produk Perikanan di Era Digital - Yapanto, Lis M (Abdurrauf Science and Society, 2025)
Digital transformation has changed the way businesses market their products, including in the fisheries sector. This article examines the fisheries product marketing system in the digital era through descriptive-qualitative and quantitative approaches, using case studies of fisheries MSMEs in Indonesia. The results show that digital platforms such as e-commerce, social media, and integrated logistics applications play a significant role in increasing market access, distribution efficiency, and product added value. However, challenges such as limited digital literacy and infrastructure remain major obstacles. Strategic recommendations include increasing the digital capacity of businesses, integrating supply chain systems, and supporting government policies. Transformasi digital telah mengubah cara pelaku usaha memasarkan produk, termasuk dalam sektor perikanan. Artikel ini mengkaji sistem pemasaran produk perikanan di era digital melalui pendekatan deskriptif-kualitatif dan kuantitatif dengan studi kasus pada pelaku UMKM perikanan di Indonesia. Hasil penelitian menunjukkan bahwa platform digital seperti e-commerce, media sosial, dan aplikasi logistik terintegrasi memiliki peran signifikan dalam meningkatkan akses pasar, efisiensi distribusi, dan nilai tambah produk. Namun, tantangan seperti keterbatasan literasi digital dan infrastruktur masih menjadi kendala utama. Rekomendasi strategis mencakup peningkatan kapasitas digital pelaku usaha, integrasi sistem rantai pasok, dan dukungan kebijakan pemerintah.